Housing production in Brussels: the neighbourhood city to stand the test of urban densification - Priscilla Ananian (Brussels Studies)
In recent years, housing densification in the Brussels-Capital Region has become an urban development issue and tool to cope with demographic expansion and the widening gap between supply and demand as regards social and middle income housing. The choice of location is crucial in order to meet these challenges, identified in particular in the Sustainable Regional Development Plan project. Yet, with a social housing stock of 39 000 dwellings and more than 45 000 prospective tenant households, public real estate developers do not seem to consider location as a priority criterion to decide on new housing operations in the regional territory. The present article is intended to be an updated summary of research which began approximately ten years ago and whose objective was to analyse public and private housing production since 1989 with regard to the evolution of the city project [Ananian, 2010]. A second objective has been added to this initial one, namely to compare these results to the Regional Housing Plan (2005) production and the financial framework of Alliance Habitat (2015). This synopsis highlights the necessity to direct the efforts of the public authorities towards an integrated strategy of urban planning and public housing production which takes into account the proximity of the facilities, services and amenities of daily life.